Assessment of the reliability of at-home caregiver-collected anthropometric measurements - Ly, Jenny J.; Sosa, Ana; Heidman, Matthew; Dixon, Matthew F.; Ostolaza, Christian; Dallabrida, Susan M. (Frontiers in Pediatrics, 2024)
Introduction: Anthropometric measurements provide valuable information about infants' growth patterns and may help identify nutrition, growth, and developmental concerns. With increasing use of telehealth and decentralized clinical trial approach, there is potential for caregivers to collect anthropometric measurements at home via teleconference with healthcare professionals (HCPs) to monitor infants' growth, which indirectly refer to health status conditions. This study sought to evaluate whether telehealth-guided caregivers can utilize standardized methods and home-use measurement equipment to collect reliable anthropometric measurements in comparison to HCPs and study nurses. The study compared weight, length, and head circumference measurements collected by caregivers (n=8 pairs), pediatric HCPs (n=7), and study nurses (n=4) as the gold standard comparator group. Four silicone dolls of varied anthropometrics were measured in surrogate of human infants. Results: Caregiver inter-and intra-observed technical error of measurement (TEM) were all equal to or below the maximum allowed error (MAE). For HCPs, only intra-observer TEM for length and inter-observer TEM for HC and length were within MAE. There was no evidence of bias for either caregiver or HCP measurements compared to the gold standard. Coefficients of reliability (R) were greater than 0.96 for all measurements. Discussion: Preliminary results from this study demonstrate that telehealth-guided caregivers can capture accurate and reliable anthropometric measurements compared to HCPs. Results suggest the use of remote measurement collection, which allows for more frequent monitoring while reducing patient and caregiver burden in primary care and clinical trials such as infant formula growth monitoring studies.